Strategi Komunikasi Publik Relation Dalam Mempromosikan Pariwisata - Farkhan Huzein (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Indonesia is a country rich in culture, language, natural resources and human resources. With this wealth, Indonesia is able to attract domestic and foreign visitors to the regions. Indonesia's foreign exchange earnings are significantly supported by the tourism industry By promoting tourism, it is hoped that it can attract tourists from foreign countries to come to travel. So the need for public relations actors in promoting tourism and the need for effective strategies. This research uses qualitative methodology and uses books, journals, and articles as sources for document analysis. The data is examined descriptively. This research method uses literature sources. Information was gathered from literature sources, including works from journals and publications that support the idea of how to reconcile religion and science. The method used in reading the journal works was to use content analysis in a descriptive manner. Sources were taken from several journals and articles. In conclusion, this article was created with the aim of providing strategies for PR actors in promoting a tour.